(untitled) (Research, Society and Development, 2021)
The effect of resveratrol supplementation on fresh (E1) or vitrified/warmed (E2) in vitro produced bovine embryos was investigated by evaluating the time-dependent response. After in vitro production, resveratrol (0.5 µM) was added to the incubation media and after two incubation periods with or without resveratrol, blastocysts were re-cultured for 24h. The rates of re-expansion, hatching, total cell number (TCN), apoptotic cells (ACN), reactive oxygen species (ROS) and intracellular glutathione (GSH) content were evaluated. For E1, the re-expansion rate differed at 6 and 10h within and between treatments (P<0.05), as did the re-expansion rate after 24h (P<0.01). The hatching rate increased after 10h with resveratrol (P<0.01) with differences within (P<0.05), but not between treatments after 24h of re-cultivation. At E2, hatching rate differed between treatments at 24h (P<0.01), with higher TCN in resveratrol-treated blastocysts after 10h (P<0.01). Resveratrol supplementation reduced ROS generation in E1 and E2 after 10h of incubation and increased GSH content (P<0.01). These results indicate that supplementation of holding re-cultivation medium with resveratrol for treatment of fresh or vitrified/warmed in vitro produced bovine embryos has a positive and time-dependent effect. The reduction of ROS content, the increase of GSH and the anti-apoptotic ability of resveratrol are responsible for its protective effects, allowing an extension of embryo storage time before transfer to recipients.